(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article provides a comprehensive overview of political parties and the electoral process, focusing on the actions and strategies employed during elections. It explores the key steps involved in elections, including voter registration, candidate nominations, campaigning, voting, and result certification. Additionally, it discusses various actions and strategies that political parties and candidates use to maximize their chances of success, such as platform development, fundraising, grassroots mobilization, media engagement, voter targeting, coalition building, and data analysis. The article highlights the importance of political parties in democratic systems and emphasizes the dynamic nature of election campaigns.